2021
DOI: 10.3390/sci3040039
|View full text |Cite
|
Sign up to set email alerts
|

Graph Coverings for Investigating Non Local Structures in Proteins, Music and Poems

Abstract: We explore the structural similarities in three different languages, first in the protein language whose primary letters are the amino acids, second in the musical language whose primary letters are the notes, and third in the poetry language whose primary letters are the alphabet. For proteins, the non local (secondary) letters are the types of foldings in space (α-helices, β-sheets, etc.); for music, one is dealing with clear-cut repetition units called musical forms and for poems the structure consists of g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…[22] and ( [23] p. 90) and follows from the fact that π 2 is not a free group. The group f p is close to π 2 in the sense that the cardinality sequence [1,3,10,51,164,1365,9422,81594, 721305, • • • ] of the cc of subgroups is that of π 2 , up to the higher index 9 that we could reach in our calculations.…”
Section: The Dna-binding Domain Mycmentioning
confidence: 62%
See 3 more Smart Citations
“…[22] and ( [23] p. 90) and follows from the fact that π 2 is not a free group. The group f p is close to π 2 in the sense that the cardinality sequence [1,3,10,51,164,1365,9422,81594, 721305, • • • ] of the cc of subgroups is that of π 2 , up to the higher index 9 that we could reach in our calculations.…”
Section: The Dna-binding Domain Mycmentioning
confidence: 62%
“…The central portion of the protein contains 86 = 30 + 28 + 28 aa decomposed into 3 zinc fingers with the following secondary structure (letter H is for the α-helix segment, letter E is for the β-sheet segment and letter C is for the random coil segment) CCCEECCCCCCCCEECHHHHHHHHHHHHHH CCCEECCCCCCEECHHHHH-HHHHHHHHH CCCEECCCCCCEECHHHHHHHHHHHHHC Taking the former 3-letter chain as the relation of a finitely generated group on 3 letters (and rank 2), we get the cardinality sequence for the cc of its subgroups as [1,3,7,26,112, 717, • • • ], which fits the cardinality sequence of cc of subgroups of the free group F 2 only up to the index 4.…”
Section: The Dna-binding Domain Egr1mentioning
confidence: 99%
See 2 more Smart Citations
“…The remote principle envisaged by Plotinus is still a symmetry principle but in a modern definition involving group theory and algebraic geometry. Recently, we wrote a paper about a common algebra possibly ruling the beauty and structure in poems, music and proteins [2]. We found that free groups govern the structure of such disparate topics where a language emerges from pure randomness.…”
Section: Introductionmentioning
confidence: 99%